Palpable Purpura with an Unexpected Outcome - Anne Friesgaard Christensen; Ole Clemmensen; Peter Junker (Case Reports in Rheumatology)
Scurvy is a potentially lethal condition caused by inadequate vitamin C intake. Hypovitaminosis of vitamin C causes vessel fragility and follicular hyperkeratosis that can lead to palpable purpuric skin lesions. In this case report, we aim to remind readers that scurvy still occurs in Western countries and that the clinical presentation may resemble vasculitis.